2023
DOI: 10.5851/kosfa.2022.e67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extract of Perilla Leaves on the Quality Characteristics and Polycyclic Aromatic Hydrocarbons of Charcoal Barbecued Pork Patty

Abstract: This study aimed to investigate the effect of ethanolic extracts from perilla leaves (PLE) on the quality attributes and polycyclic aromatic hydrocarbons (PAHs) in charcoalbarbecued pork patties. The PLE addition and doneness had no significant effect on the pH of pork patties (P > 0.05). Regardless of the concentration, the PLE significantly lower malondialdehyde concentrations and reduced the CIE L*, a*, and b* values when compared to control. The addition of 0.2% of PLE did not adversely affect the organole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This finding supports Soeparno's [11] statement, as observed in the current study's results. The WHC value obtained in this research is in the range of 59.87 to 85.51%, which confirms previous studies [2,8,11].…”
Section: Water Holding Capacity (Whc)supporting
confidence: 92%
See 2 more Smart Citations
“…This finding supports Soeparno's [11] statement, as observed in the current study's results. The WHC value obtained in this research is in the range of 59.87 to 85.51%, which confirms previous studies [2,8,11].…”
Section: Water Holding Capacity (Whc)supporting
confidence: 92%
“…The improved meat tenderness is a consequence of complex reactions and protein degradation that affect the structure of myofibrillar proteins. Various reports mentioned the dissociation of actomyosin, along with the degradation of main proteins including nebulin, troponin-T, dystrophin, desmin, and titin [6,7,8]. However, due to potential detrimental effects from continuous and excessive consumption of STPP including stomach discomfort, nausea, or even stomachache, the Food and Drug Administration limit the maximum use of STPP to around 0,5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary mechanism of inhibiting the generation of PAHs and N-nitroso compounds is the ability of antioxidants to scavenge free radicals [ 66 , 77 ]. Cho et al [ 78 ] demonstrated that the addition of a 0.4% Perilla frutescens extract to pork patties hindered both lipid oxidation and PAH formation. Similarly, Shen et al [ 79 ] found that adding 2.5% green tea extract to roasted ducks substantially suppressed PAH formation by 79.7%, owing to its abundant phenol content.…”
Section: Reinforcement Of Nutritional Valuementioning
confidence: 99%
“…They lower the excretion rate of eggs and larvae by adult worms and the impairment of larvae development into further stages of life (Rodríguez-Hernández et al 2023). Besides, various plants containing tannins are reported to possess antimicrobial activity by protecting proteins from degradation caused by microorganisms (Nawab et al 2020;Cho et al 2022;Cho et al 2023).…”
Section: Introductionmentioning
confidence: 99%